PKM PEMBERDAYAAN EKONOMI PEMUDA MELALUI PEMBENTUKAAN KOPERASI KARANG TARUNA DI KOTA TANGERANG - Yudi Nur Supriadi; Jubaedah Jubaedah; Munasiron Munasiron; Ivan Yulivan; Rachmi Rachmi; Eki Juniardi (LPPM Universitas Bina Bangsa, 2022)
Youth has a central role in overseeing the development journey, The role played by youth in the economic field is able to be optimally actualized as we all expect. The establishment of the Karang Taruna Cooperative, Jatiuwung District, Tagerang City, is predicted to be able to provide the welfare of members and the surrounding community. The process of empowering youth through the Karang Taruna Cooperative is implemented through Community Service (PKM) activities to provide empirical ideas for real work for the economic progress of more independent youth. Economic empowerment through the Karang Taruna cooperative can create an integrated unity between the role of the campus and the community, especially the PKM Team of UPN Veteran Jakarta Lecturers with Karang Taruna, Jatiuuwung District, Tangerang City. In the process, there are problems faced by the youth economy including: a). Not understanding the meaning and importance of Cooperatives for youth economic empowerment b). Do not yet understand running good cooperative management, c). Not optimal business run by Taruna reefs. Departing from the real problems and conditions of the role of youth for the economy to increase, it is necessary to support the activities and stages of implementing Youth Cooperatives such as getting to know the types of cooperatives, cooperative groups, cooperative businesses and knowing how to manage cooperatives properly and correctly. Furthermore, it is necessary to give an understanding of the conditions for establishing a cooperative. Understanding in preparing documents in the form of a license that must be owned by the cooperative if it is established and the business is already running. Participants will be given a stamp on cooperative management, cooperative working capital consisting of principal deposits, compulsory deposits and voluntary deposits, all of which come from members. After that, participants were given material on calculating the remaining business results that must be distributed to members every year known as SHU and the Annual Member Meeting (RAT) which must be held by the management every year. Thus, it can be seen that the impact of the Karang Taruna Cooperative needs to provide benefits for the suisnability of the youth's business. Therefore, the Karang Taruna Jatiuwung Cooperative in Tangerang City is able to improve the economy of members and the community by being free from poverty in order to improve their standard of living independently